Amidination of lipase with hydrophobic imidoesters - Basri, M.; Ampon, K.; Yunus, W. M. Z.; Razak, C. N. A.; Salleh, A. B. (Wiley, 1992)
Lipase from Candida rugosa was chemically modified by amidination with imidoester hydrochlorides of different hydrophobicity. The modified enzyme showed a higher ester synthesis activity but a lower ester hydrolysis activity compared with the native enzyme. The maximum specific activity of the modified enzyme depended on its degree of derivatization. Benzene was found to be the best solvent for the synthesis reaction. The optimal temperature for the reaction was not affected by modification of the lipase. The modified lipase was more thermostable and solvent-stable than the native enzyme. When fatty acids of different carbon chainlength were tested as substrates in the synthesis of esters with the modified lipase, the highest activity was observed with myristic acid and propanol.